2016
DOI: 10.1364/optica.3.001241
|View full text |Cite
|
Sign up to set email alerts
|

Multipolar nonlinear nanophotonics

Abstract: Nonlinear nanophotonics is a rapidly developing field with many useful applications for a design of nonlinear nanoantennas, light sources, nanolasers, sensors, and ultrafast miniature metadevices. A tight confinement of the local electromagnetic fields in resonant photonic nanostructures can boost nonlinear optical effects, thus offering versatile opportunities for subwavelength control of light. To achieve the desired functionalities, it is essential to gain flexible control over the near-and far-field proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
282
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 322 publications
(293 citation statements)
references
References 213 publications
(310 reference statements)
2
282
0
2
Order By: Relevance
“…We have reviewed a few of the representative demonstrations of metasurface‐based devices such as wave plates, polarimetries, metalenses, metaholograms, and optical vortex converters, and these examples are listed in Table 3 - 6 . There are still many other aspects or applications not included here, such as nonlinear metasurfaces, hyperbolic metasurfaces, thin‐film metasurfaces, parity–time symmetry metasurfaces, etc. Thanks to the advances in nanofabrication technologies, these low‐cost, large‐area, and mass‐productive techniques have sped up the development of static metadevices and are gradually becoming mature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reviewed a few of the representative demonstrations of metasurface‐based devices such as wave plates, polarimetries, metalenses, metaholograms, and optical vortex converters, and these examples are listed in Table 3 - 6 . There are still many other aspects or applications not included here, such as nonlinear metasurfaces, hyperbolic metasurfaces, thin‐film metasurfaces, parity–time symmetry metasurfaces, etc. Thanks to the advances in nanofabrication technologies, these low‐cost, large‐area, and mass‐productive techniques have sped up the development of static metadevices and are gradually becoming mature.…”
Section: Discussionmentioning
confidence: 99%
“…There are still many other aspects or applications not included here, such as nonlinear metasurfaces, [129][130][131][132][133][134][135][136][137][138][139][140][141] hyperbolic metasurfaces, [142][143][144][145][146][147][148] thin-film metasurfaces, [149][150][151][152][153][154][155] parity-time symmetry metasurfaces, [156][157][158][159] etc. Thanks to the advances in nanofabrication technologies, these low-cost, large-area, and mass-productive techniques have sped up the development of static metadevices and are gradually becoming mature.…”
Section: -6mentioning
confidence: 99%
“…111 The presence of both electric and magnetic nonlinearities enhances the interference effects, which in turn increases the efficiency and controls the polarization of the nonlinear processes, as well. 89,112 Another important resonance mode that can be achieved in dielectric nanostructures by possessing more complex design is the Fano resonance. 113,114 The Fano resonance is considered This is an additional degree of freedom to manipulate the magnetic resonances of dielectric nanostructures to enhance the nonlinear interaction.…”
Section: Multipolar Resonances In All-dielectric Systemsmentioning
confidence: 99%
“…When the toroidal and electric dipole modes spectrally overlap, they produce almost equivalent radiation patterns in the far field but with opposite phases, generating a pronounced dip in the spectrum (Figure 1 are able to withstand much higher pump fields making them promising to obtain higher nonlinear conversion efficiencies. 89,91,120 The electric field enhancement in dielectric nanostructures is typically smaller than in the plasmonic ones, however, the additional volume resonance can be added to make the overall enhancement larger, as the field confinement in dielectric nanostructures is not restricted to the surface only as in their metallic counterparts.…”
Section: Multipolar Resonances In All-dielectric Systemsmentioning
confidence: 99%
“…[1][2][3][4] In recent years, optical antennas have attracted considerable interest and hold promise to improve the performance in a large number of applications, such as near-field scanning optical microscopy, 5 photo-detectors, 6 photovoltaic cells, 7 thermal emitters, 8 saturable absorbers, 9 upconverted incoherent nonlinear emission, 10,11 single-molecule fluorescence enhancement, 12 and third harmonic generation (THG) enhancement. 13 Due to the lightning-rod effect and the coupling of two metal nanotriangles (coupled plasmons), it has been shown that bowtie nanoantennas 14 can achieve stronger intensity enhancement than other comparable structures such as rod-, ellipse-, disk-, and cross-shaped nanoantennas.…”
mentioning
confidence: 99%